Present Status and Conservative Strategy of "Piramanthanaru" in Visuvamadu, Kilinochi District - A Field Survey - Sathiyaseelan, V.; Beron, V.A. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2017)
Siddha system is the ancient Dravidian system of medicine. The word "Siddha medicine" means established truth. In practice generally the plants used often in the compound form to which either herbs, metals, minerals and animals products are added, but mostly herbs are the common ingredients of siddha drugs. Objective of my study is "Present status and conservative strategy of Piramanthanaru in Visuvamadu, Kilinochi district". The research was carried out on June 2017. The area map was used to record the medicinal plants. Siddha literatures were used to analyzed the medicinal plants. 95 medicinal plants were identified in the significant area. Among this 95 medicinal plants according to the taxonomical morphology 26 (27.36%) are big trees, 19 (20%) are small trees, 14 (14.73%) are herbs, 15 (15.78%) are shrubs, 10 (10.52%) are climbers, 7 (7.36%) are moderate trees and 4 (4.21%) are creepers. Based on their self-span 67 (70.5%) plants are perennial, 12 (12.63%) are biannual and 11 (11.37%) are annual plants. Through my study I discovered 79 (83.16%) are common and 16 (16.84%) are rare for this zone. Among this 95 medicinal plants 4 (4.21%) are spinaches 4 (4.21%) are poisonous plants and 3 (3.75%) are rejuvenating herbs. According to the siddha pharmacodynamics, among this 95 medicinal plants 65 (68.42%) plants have hot in potency (Thanmai) and 30 (31.57%) have cold in potency. From this survey I found 67 (70.52%) plants have the post digestive effect (Vipakam) of bitter and 28 (29.47%) have sweet effect. According to the taste (Suvai) among this 95 plants 57 (60%) plants contains bitter taste, 39 (41.05%) are astringent taste, 28 (29.47%) are sweet taste, 13 (13.68%) are pungent taste, 4 (4.21%) are sour taste and there has no salt taste plants in this zone. According to the parts used of medicine from this 95 medicinal plants 39 (41%) plants' leaves 24 (25.2%) roots, 19 (20%) fruits, 17 (17.8%) bark, 17 (17.8%) flowers, 8 (8.4%) root bark, 8 (8.4%) whole plants, 2 (2.1%) buds are used for medicine. According to the secretions of the medicinal plants, 2 (2.1%) secrete gum and 2 (2.1%) secrete latex, 1 (1.05%) secrete resins and 4 (1.05%) secrete goals. This paper attempts to give awareness on conservation of medicinal plants, gives the present status of medicinal plants in the Piramanthanaru area. I suggest to declare this significant zone as a protectable zone and the steps should be taken against destroy of the medicinal plants and also the farmers should be encouraged to cultivate the possible medicinal plants in a proper way in this significant zone. Through my study I discovered many plants which identified in this zone are most important, very useful and rare plants for treating lots of diseases. I suggest the government can be built indigenous treatment centre in this surrounding area and give curative treatments with natural therapy in this natural site and also I think this is one of an attempt to increase the tourism income also.
Keywords: Piramanthanaru; Conservation; Strategy